Adherence to folic acid supplementation among children with sickle cell disease diagnosed through the newborn screening program: associated factors. (Research, Society and Development, 2022)
Introduction: Folic acid is used as a prophylactic therapy in haemolytic anaemia. Low adherence to folic acid in children with sickle cell disease contributes to the emergence of complications and worsening of health, and thus an increase in care costs. Objective: To analyse medication adherence to folic acid in children with sickle cell disease, haemoglobin SS (HbSS) or SC (HbSC), diagnosed by neonatal screening. Methods: Cross-sectional study, by measurements of serum folate levels in children and application of the Morisky-Green Test (MGT) and Brief Medication Questionnaire (BMQ) to caregivers. Results: There were 34.0% and 40.4% of “adherents” for MGT and BMQ. Elevated serum folate was found in 78.7% of the participants, and none of them had deficiency. Pharmaceutical form (p=0.719), age group (p=0.875), income (p=0.944) and caregiver’s education (p=0.070) were not associated factors to adherence. HbSS patients record more than four times the adherence of HbSC (48.3% vs. 11.1%; p=0.012). Difficulty of access to the medication and interruption/lagging of treatment were the main contributors to non-adherence. Conclusion: There was a contrast between the adherence reported by the questionnaires and the high serum folate levels.